Economics For Business - David Begg; Damian Ward (London McGraw-Hill Education, 2019)
Economics for Business now in its 6th edition remains an essential introduction to economics for business students. It provides an accessible guide to the practical uses of economics and covers topics on the global economy, GDP growth as a policy, the rise of populism and Brexit.
Keywords: Economics; Business; Textbooks; The International Market Environment (ECO1021-N)